Diastereocontrolled synthesis of hydroxylated lactams - Andrews, MD; Brewster, A; Moloney, M (2002)
Highly diastereoselective reductions and organometallic additions in bicyclic lactams have been observed, which appear to result either from a stereoelectronic interaction of the pyramidalised nitrogen lone pair or from steric interactions in the bicyclic system. These products can be readily deprotected to give hydroxylated lactams.